QORAQALPOG‘ISTONLI TURKMANLAR TILIGA YEVROPA TILLARIDAN O‘ZLASHGAN SO‘ZLAR - Babaeva, M.A.; Chariev, Ch.D. (SCIENCE and SOCIETY, 2024)
The article provides the analysis of words borrowed to the Turkmen language from European languages, and several examples in which areas these words are actively used.
Keywords: borrowed words from European languages; foreign languages; term; borrowed terms; semantics of borrowed words